Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/vru.12194
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Diagnosis—urinary Bladder Duplication in a Cat

Abstract: A female kitten presented for chronic, intermittent, antibiotic-responsive urinary incontinence and chronic kidney disease. Abdominal ultrasound identified bilateral pelvic/ureteral dilation and three closely apposed thin-walled fluid-filled structures in the caudal abdomen, extending toward the pelvic inlet. Excretory urography and negative contrast cystography identified contrast medium accumulation from the dilated ureters into two tubular soft tissue masses of the caudal abdomen, with subsequent gradual fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 19 publications
(34 reference statements)
1
24
0
Order By: Relevance
“…Congenital abnormalities accounted for only 18% of our series of incontinent cats and included 4 cats with congenital spinal canal malformations (eg, Manx syndrome or spinal dysraphism), 1 cat with bilateral ureteral ectopia, 2 cats with presumed congenital USMI, and 1 cat with urethral hypoplasia . These and other congenital causes of UI in cats have been reported previously . It is difficult to draw conclusions on the proportional morbidity of congenital disorders in our series of cats because of relatively small numbers of affected cats and the fact that previous studies rarely reported congenital spinal cord diseases.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Congenital abnormalities accounted for only 18% of our series of incontinent cats and included 4 cats with congenital spinal canal malformations (eg, Manx syndrome or spinal dysraphism), 1 cat with bilateral ureteral ectopia, 2 cats with presumed congenital USMI, and 1 cat with urethral hypoplasia . These and other congenital causes of UI in cats have been reported previously . It is difficult to draw conclusions on the proportional morbidity of congenital disorders in our series of cats because of relatively small numbers of affected cats and the fact that previous studies rarely reported congenital spinal cord diseases.…”
Section: Discussionmentioning
confidence: 91%
“…In our series of cats, UI was associated with a variety of congenital and acquired disorders that affected both phases of micturition with similar frequency. The proportional morbidity of causes, sex, age distribution, and outcomes of UI in our series of cats differed substantially from previous reports of UI in cats and dogs . Our observations indicated that spinal cord disorders were a common cause of UI in cats and were associated with less favorable outcomes compared to bladder and urethral disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are no previous reports of complete duplication of the urinary tract in veterinary medicine, there are reported cases of duplication of various parts of the tract including the kidney, ureter, bladder, and urethra. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Duplex kidney is a commonly encountered abnormality of renal development in human medicine, with an incidence of approximately 1%. 17 A complete duplex kidney is defined as two separate pelvicalyceal systems that have arisen from two ureteral buds from the mesonephric duct.…”
Section: Introductionmentioning
confidence: 99%
“…18 Bladder duplication has been described in isolation in one cat and one dog. [7][8] In one case report, bladder duplication was also reported associated with multiple anomalies including diphallia, cryptorchidism, renal hypoplasia, and bifurcation of the descending colon. 9 Urethral duplication without associated diphallia has been described three times in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%